2019
DOI: 10.2478/fhort-2019-0030
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of some physico-chemical parameters of kiwiberry (Actinidia arguta) cultivars from a cold climate

Abstract: The Actinidia genus includes a number of commercial fruit species with a wide range of countries of origin. Some species such as A. arguta or A. kolomikta are characterized by a high level of resistance to frost. The aim of this study was to compare the fruit of selected cultivars of kiwiberry. In the kiwiberry fruit, sucrose was the predominant type of sugar. Citric acid was dominant in all samples; it was most represented in the pulp of kiwiberry seedlings and in the skin of kiwiberry ‘Issai’. Kiwiberry frui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…e SSC in kiwifruit juice was recorded on a digital Brixmeter (RA-250WE, KYOTO, Tokyo, Japan) and specified in°B rix. TA content was analyzed by the titration with 0.1 M NaOH and expressed in terms of the percentage of citric acid following the method described by Horak et al [25].…”
Section: Evaluation Of Weight Loss Fresh Firmness Total Soluble Solmentioning
confidence: 99%
See 1 more Smart Citation
“…e SSC in kiwifruit juice was recorded on a digital Brixmeter (RA-250WE, KYOTO, Tokyo, Japan) and specified in°B rix. TA content was analyzed by the titration with 0.1 M NaOH and expressed in terms of the percentage of citric acid following the method described by Horak et al [25].…”
Section: Evaluation Of Weight Loss Fresh Firmness Total Soluble Solmentioning
confidence: 99%
“…e DPPH scavenging capacity was carried out according to a previous method described by Horak et al [25]. 100 μL of extracted juice was added to 1.9 mL of 0.1 mM DPPH solution (dissolved in ethanol) and then left in the dark at 25°C for 30 min.…”
Section: Assay Of 22-diphenyl-1-picrylhydrazyl (Dpph) Scavenging Capmentioning
confidence: 99%
“…In contrast, the skin of the kiwi berry is mostly smooth and without hair, which makes the whole fruit suitable for direct consumption without removing the skin (Jackson and Harker, 1997). The intake of antioxidants in kiwi berries is nearly three times higher than that in kiwifruit (Horák et al, 2019). Previous study has reported the phenolics, ascorbate, and antioxidant potency of peel and flesh extracts of kiwi berry (Latocha, 2015); however, the peroxyl radical scavenging capacity (PSC) and cellular antioxidant activity (CAA) have not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Kiwi berry is also a medicinal and edible homologous plant, its fruit, stem, root, and leaves all have therapeutic significance [27] . The kiwi berry's polysaccharides and flavonoids moisten the intestines and cleanse the bowels [28] .…”
Section: Publishing Services By Tsinghua University Pressmentioning
confidence: 99%